On (Conflating) Predatory Journals and Compromised Research Practices: Presenting the Tool ‘Compass to Publish’ and the (Im)possible Scalability Debate - Dony, Christophe (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2025)
This commentary critically presents and discusses some of the information-literacy and pedagogical principles underlying the development of ‘Compass to Publish’, a free online tool which helps users determine the possible predatory nature of open access journals requiring or hiding article processing charges (APCs). It then moves on to discuss the limits of the tool in terms of scalability possibilities based on user feedback. Finally, the commentary shares critical observations regarding the difficulties for future developments of the tool as they can relate to compromised research practices such as paper mill activity, authorship for sale, or fake peer review.